Surgical Intervention Of Z-Plasty Frenulum Technique In The Fixed Orthodontic Treatment Of Patients With Oligodontia - Handoko, Evan Kurniawan; Karina, Vincensia Maria; Suryahapsari, Nastiti Mayangjati (Faculty of Dentistry, Universitas Islam Sultan Agung, 2024)
Background: Oligodontia is a genetic disorder in which the individual does not have more than six teeth either permanent, deciduous, or both teeth. This condition causes multiple diastemas and requires orthodontic treatment. Abnormal attachment of the superior labial frenulum also causes midline diastema, and recurrence of diastema after orthodontic treatment. Z-plasty frenectomy is commonly used for patients with thick frenulum and shallow vestibule. The presence of two transposed flaps in this technique can provide stress distribution in the tissue to minimize the occurrence of scar tissue formation. Case Report: A female patient, 20 years old and systemically healthy, came to RSGM Prof. Soedomo with complaints of a maxillary front tooth gap that disturbed her self-confidence. The patient was referred by an orthodontist colleague.Result: Clinical examination in the form of a blanch test and vestibule depth. From the examination, it was found that the patient had frenulum attachment to the anterior interdental papilla (Kotlow class III) and a shallow vestibule. In this situation, the Z-plasty technique was chosen. Satisfactory results were obtained with no scarring and no residual connective tissue that could cause diastema recurrence. Conclusion: Frenectomy using the Z-plasty technique was succeessful in removing the thick frenulum without the formation of scar tissue, and proved to be more aesthetically pleasing than other conventional methods.